Biomaterials for Interbody Fusion in Bone Tissue Engineering - Zhang, Han; Wang, Zhonghan; Wang, Yang; Li, Zuhao; Chao, Bo; Liu, Shixian; Luo, Wangwang; Jiao, Jianhang; Wu, Minfei (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, interbody fusion cages have played an important role in interbody fusion surgery for treating diseases like disc protrusion and spondylolisthesis. However, traditional cages cannot achieve satisfactory results due to their unreasonable design, poor material biocompatibility, and induced osteogenesis ability, limiting their application. There are currently 3 ways to improve the fusion effect, as follows. First, the interbody fusion cage is designed to facilitate bone ingrowth through the preliminary design. Second, choose interbody fusion cages made of different materials to meet the variable needs of interbody fusion. Finally, complete post-processing steps, such as coating the designed cage, to achieve a suitable osseointegration microstructure, and add other bioactive materials to achieve the most suitable biological microenvironment of bone tissue and improve the fusion effect. The focus of this review is on the design methods of interbody fusion cages, a comparison of the advantages and disadvantages of various materials, the influence of post-processing techniques and additional materials on interbody fusion, and the prospects for the future development of interbody fusion cages.